A closer look at the effects of restoration design on biologic function in restored estuarine wetlands: A case study in Galveston Bay, Texas. (2nd October 2019) - Dobberstine, James A.; Howard, Cynthia L.
ABSTRACT: A significant amount of coastal marsh restoration work has been implemented in estuarine coastal areas in an effort to reclaim previously degraded aquatic habitats. Design approaches vary according to numerous cost and site specific parameters. This study attempts to assess the biologic function of two common approaches to restoration site design, terracing and beneficial use islands, located within an estuarine embayment in lower Galveston Bay, Texas across a five-year timeframe. Study results indicate that there are significant differences among restoration sites by design when compared to each other and to a natural reference within the same embayment. These results suggest that advancements in restoration design have important implications for coastal habitat function and resiliency. In light of climate change, relative sea level rise, ever-present funding constraints, and the ecologic and economic importance of estuarine marsh habitat, this data will be useful for restoration managers considering applicable techniques for future projects in dynamic coastal environments.